PRIVATE LABEL: QUALITY AND LOYALTY - R.A. MARLIEN; Kasmari Kasmari; Bambang Suteja; R Basiya (STIE Pelita Nusantara Semarang, 2022)
The purpose of this research is about the loyalty of private label products, which is growing very rapidly, resulting in a decline in the market share of branded manufactured products. Private label products are products that are sold in retail stores, where these stores sell daily necessities at lower prices. Consumers who buy this product are price sensitive consumers. Although product quality is similar to manufactured products, consumers who are used to branded products have a perception of risk when buying private label products. This research was conducted at a retail store that sells products with the same brand as the name of the retail store. The research location was in Semarang and Gringsing with a sample of 120 respondents. Determination of the number of samples using purposive sampling technique, data analysis using multiple regression. The finding is that repurchase intention is an intervening variable between store image, risk perception, price perception and loyalty.